The utility and significance of minor criteria for diagnosis of atopic dermatitis in an Indian setting. - Phiske, M.M.; Pal, A.C.; Dhurat, R.S.; Jain, P. (European Journal of Pediatric Dermatology, 2016)
Hanifin and Rajka’s criteria are the gold standard for diagnosis of atopic dermatitis (AD). However, none of the major criteria is specific/restricted to AD. Thus in a case with strong clinical suspicion, minor criteria can be used as auxiliary diagnostic aid, when major criteria are uncertain. Seventy clinically suspected cases of AD (<13 years) were evaluated for major and minor clinical criteria; their diagnostic significance was statistically analyzed with seventy age-matched controls. The most frequent major criteria were atopy history (75.7% of patients) and pruritus (72.9%). Only 14 patients (20%) fulfilled at least 3 major criteria, the remainder (56 patients-80%) fulfilled less than 3 (35 patients- 2 major, 18- 1 major criteria, 3- none). The most frequent minor criteria were xerosis (75.7%), peri-follicular accentuation (40%), hand/foot dermatitis (24.3%) and scalp-scaling (21.4%). Overall, 26 patients (37.1%) fulfilled at least 3 minor criteria, irrespective of major criteria. Of these 26, only 9 children fulfilled Hanifin and Rajka’s criteria (3 major +3 minor). The remaining 17 had less than 3 major criteria. If only minor criteria were taken into consideration, these additional 17 could be diagnosed as AD. Almost all minor criteria were more frequent in children with AD as compared to controls, the difference being statistically significant (p<0.005) for xerosis, peri-follicular accentuation, Dennie-Morgan folds, hand-foot dermatitis and periorbital darkening. Patients who fulfill at least 3 minor criteria, especially the above mentioned significant ones, irrespective of number of major criteria fulfilled, should be strongly suspected to have AD.